2020
DOI: 10.1159/000506717
|View full text |Cite
|
Sign up to set email alerts
|

Can a Simple Geriatric Assessment Predict the Outcome of TURP?

Abstract: KeywordsTURP · Geriatric · Outcome · Geriatric assessment · Benign prostatic hyperplasia · Lower urinary tract symptoms Abstract Purpose: To determine the impact of a simple preoperative geriatric assessment on the outcome in older patients with recurrent urinary retention who underwent desobstructive surgery. Patients and Methods: Patients aged 75 years or older with recurrent urinary retention referred for TURP entered this prospective, multicentre study. Several demographic, intra-and postoperative paramete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…The indication for disobstructive surgery in elderly patients has to balance life expectancy, functional outcome and surgical risk [2]. Approximately, 12% of patients older than 75 years of age die within 12 months after the first episode of urinary retention and this rate increases up to 30% in nursing home patients who underwent TURP [2][3][4]. In parallel, the functional outcome decreases with advancing age with age-related detrusor underactivity being a relevant co-factor [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…The indication for disobstructive surgery in elderly patients has to balance life expectancy, functional outcome and surgical risk [2]. Approximately, 12% of patients older than 75 years of age die within 12 months after the first episode of urinary retention and this rate increases up to 30% in nursing home patients who underwent TURP [2][3][4]. In parallel, the functional outcome decreases with advancing age with age-related detrusor underactivity being a relevant co-factor [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…However, success rate of surgery was 80.6% in fit and 75% in frail patients, while 3-month success rates were 95.2% and 83.3% for non-rail and frail respectively (24). Post-Void Residual (PVR) was less than 50 ml in both cohorts (24). Pichon et al, showed that frail patients had lower success rate at 3 months (55%) compared to non-frail patients (95%) (p < 0.05) following TURP (25).…”
Section: Resultsmentioning
confidence: 86%
“…According to Soma et al frailty was positively associated with LUTS (HR: 2.13; 95%; CI: 2.48-3.06), OAB (HR: 2.07; 95%; CI: 1.31-3.29) and higher prevalence of nocturia (23). According to Eredics et al, intraoperative complications, duration of postoperative catheterization and length of hospitalization was identical in frail and non-frail patients undergoing transurethral resection of the prostate (TURP) (24). However, success rate of surgery was 80.6% in fit and 75% in frail patients, while 3-month success rates were 95.2% and 83.3% for non-rail and frail respectively (24).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We therefore aimed to prospectively evaluate validated geriatric assessment tools as predictors of functional outcomes, peri- and postoperative complications, and mortality in patients undergoing radical urological tumor surgery at the age of 70 years or older. Inspired by very simple assessments for the prediction of functional outcome in other urological surgeries [16], we created the Erlangen Index (EI), which is highly feasible and predictive for functional deterioration and mortality in major urological tumor surgery.…”
Section: Introductionmentioning
confidence: 99%